The face behind the law: The United Nations and the rights of indigenous peoples - Jackson, Moana (Yearbook of New Zealand jurisprudence, 2005)
In recent years Maori people have adopted many strategies to protect and advance the well being and visions implicit in the exercise of tino rangatiratanga. Much of that work has been done at home, but an increasing number of Iwi and other Maori organisations are now participating in international affairs that are seen to have some relevance to our lives. They are joining a worldwide movement by Indigenous Peoples to reassert their rights and reclaim their rightful place.
Keywords: UNDRIP; civil Rights; colonisation; crown law; imperialism; international law; international organization; racism; tiriti o waitangi/treaty of waitangi; waitangi tribunal

Politics, Indigenous Rights and Resource Ownership: Māori Customary Rights to the Foreshore, Seabed and Fresh Water in New Zealand - Sullivan, Ann (Studies in arts and humanities, 2017)
Māori customary rights to natural resources are a contentious issue between Māori and the New Zealand government and between Maori and non-Māori. The values and principles inherent in a treaty signed in 1840 between Māori and the British Crown have been undermined by the government’s refusal to allow Māori the right to go to the courts to determine proprietary rights to the foreshore, seabed and fresh water. Discriminatory Crown actions highlight the argument that when an injustice occurs then reparations should be made. The United Nations has chided the New Zealand government for its discriminatory behaviour and failure to provide guaranteed redress but it has had little effect.
Keywords: civil Rights; crown policy; discrimination; environment; land rights; māori rights

Indigenous peoples rights under international law - Adcock, Fleur; Charters, Claire (The New Zealand Yearbook of International Law, 2010)
In 2010 Indigenous peoples' rights continued to feature in discussions in a variety of international fora. Indigenous peoples' traditional knowledge (TK) associated with genetic resources (GR) were discussed under the Convention on Biological Diversity (CBD); under the auspices of the World Intellectual Property Office (WIPO) and within the World Trade Office (WTO). The United Nations (UN) General Assembly's Declaration on the Rights of Indigenous Peoples (Indigenous Peoples' Declaration) featured in debate under the UN Framework Convention on Climate Change (UNFCCC); the UN General Assembly's Third Committee; the work of the UN mechanisms with a specific mandate concerning Indigenous peoples; and, in a landmark ruling of the African Commission on Human and People's Rights (African Commission), was adopted by the African Union. International human rights monitoring bodies also advanced their jurisprudence on the rights of Indigenous peoples.
Keywords: UNDRIP; civil Rights; crown policy; discrimination; takutai moana; tiriti o waitangi/treaty of waitangi; united nations

An Imbalance of Powers: Maori Land Claims and an Unchecked Parliament - Charters, Claire (Cultural Survival, 2010)
Aotearoa/New Zealand is not known for egregious breaches of indigenous peoples’ rights. Nonetheless, New Zealand’s legal system is ineffective at implementing international and domestic laws that protect the rights of Maori. This has been seen most starkly in the Foreshore and Seabed Act of 2004, which had the effect of extinguishing Maori aboriginal title to the foreshore and seabed areas and was passed despite almost universal Maori opposition.
Keywords: civil Rights; constitution; crown policy; foreshore and seabed act 2004; parliament; tiriti o waitangi/treaty of waitangi; treaty settlements

Report from the inside: the CERD Committee's review of the Foreshore and Seabed Act 2004 - Charters, Claire; Erueti, Andrew (Law review (Wellington), 2005)
Describes, from the perspective of the advocates for Maori claimants, the substance of submissions to and process followed by the United Nations committee on the Elimination of Racial Discrimination (CERD) in determining that the Foreshore and Seabed Act 2004 discriminates against Maori. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: civil Rights; crown law; foreshore and seabed act 2004; human rights; international law; international organization; land rights; land tenure; racism

Price of citizenship for Maori: A matter of historical and legal context - Warbrick, Paerau (Law & History, 2021)
This article explains that the concept of citizenship for Maori in New Zealand has evolved. The 'Native Rights Act 1865' declared all Maori to be subjects of the Crown. This implication then justified the confiscation of lands in the 1860s from those Maori deemed to be disloyal to the Crown. By the beginning of the twentieth century, politicians began to use the concept of citizenship to force Maori to fight in World War I. In the mid-twentieth century, the Maori politician Apirana Ngata used the term 'price of citizenship' to gain social and political rights for all Maori, as a result of the efforts of Maori soldiers fighting as New Zealand citizens in World War II.
Keywords: citizenship; civil Rights; colonisation; military

Perceived discrimination predicts increased support for political rights and life satisfaction mediated by ethnic identity: A longitudinal analysis - Stronge, Samantha; Sengupta, Nikhil K.; Barlow, Fiona Kate; Osborne, Danny; Houkamau, Carla A.; Sibley, Chris G. (Cultural Diversity and Ethnic Minority Psychology, 2016)
Objectives: The aim of the current research is to test predictions derived from the rejection-identification model and research on collective action using cross-sectional (Study 1) and longitudinal (Study 2) methods. Specifically, an integration of these 2 literatures suggests that recognition of discrimination can have simultaneous positive relationships with well-being and engagement in collective action via the formation of a strong ingroup identity. Method: We test these predictions in 2 studies using data from a large national probability sample of Māori (the indigenous peoples of New Zealand), collected as part of the New Zealand Attitudes and Values Study (Ns for Study 1 and 2 were 1,981 and 1,373, respectively). Results: Consistent with the extant research, Study 1 showed that perceived discrimination was directly linked with decreased life satisfaction, but indirectly linked with increased life satisfaction through higher levels of ethnic identification. Perceived discrimination was also directly linked with increased support for Māori rights and indirectly linked with increased support for Māori rights through higher levels of ethnic identification. Study 2 replicated these findings using longitudinal data and identified multiple bidirectional paths between perceived discrimination, ethnic identity, well-being, and support for collective action. Conclusion: These findings replicate and extend the rejection-identification model in a novel cultural context by demonstrating via cross-sectional (Study 1) and longitudinal (Study 2) analyses that the recognition of discrimination can both motivate support for political rights and increase well-being by strengthening ingroup identity. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Keywords: civil Rights; community; discrimination; ethnic identity; hauora; identity; protest

Māori, a politicized identity: Indigenous identity, voter turnout, protest, and political party support in Aotearoa New Zealand - Greaves, Lara M.; Sengupta, Nikhil K.; Townrow, Carly S.; Osborne, Danny; Houkamau, Carla A.; Sibley, Chris G. (International Perspectives in Psychology: Research, Practice, Consultation, 2018)
Political struggles are important to the identities of many indigenous peoples. This article examines identity as a predictor of crucial political outcomes—voter turnout, support for protest, and political party support—for Māori, the indigenous peoples of Aotearoa (New Zealand). We analyzed data from a national probability sample of Māori (N = 663) that included a scale of subjective identification with various aspects of Māori identity: the Multidimensional Model of Māori Identity and Cultural Engagement. Use of the scale allowed us to examine the facets of ethnic identity that predict political mobilization for indigenous peoples. As expected, the identity domain relating to political struggle, Socio-Political Consciousness, was positively associated with support for left-wing parties and Māori rights protest but negatively associated with support for the right-wing party. However, Socio-Political Consciousness did not relate to voter turnout. These results demonstrate the importance of ethnic identity as a key predictor of political behaviors for indigenous peoples. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Keywords: civil Rights; ethnic identity; kāwanatanga; political participation; political parties; voter turnout; voting